2005
DOI: 10.2176/nmc.45.25
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Anatomy of the Cervical Carotid Artery for Carotid Endarterectomy

Abstract: Carotid endarterectomy (CEA) is the main treatment for atherosclerotic plaque of the cervical internal carotid artery. The surgical anatomy of the carotid arteries was studied in the carotid triangle of 49 cadavers. The carotid bifurcation was located at the level of the lower third of C-3. The superior thyroid artery arose from the anterior wall of the external carotid artery in 70% of specimens and from the distal portion of the common carotid artery in 30%. The lingual artery arose as a separate trunk betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
99
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 14 publications
9
99
2
5
Order By: Relevance
“…The level of bifurcation according to the research done in Kenya on 40 cadavers was symmetrical in all cases [7], and another study done in Japan, Tokyo, on 49 cadavers found no difference in level between the two sides in all cases [13].…”
Section: Side Symmetry Of Cca Bifurcationmentioning
confidence: 90%
See 1 more Smart Citation
“…The level of bifurcation according to the research done in Kenya on 40 cadavers was symmetrical in all cases [7], and another study done in Japan, Tokyo, on 49 cadavers found no difference in level between the two sides in all cases [13].…”
Section: Side Symmetry Of Cca Bifurcationmentioning
confidence: 90%
“…A high common carotid artery bifurcation possesses a higher risk of being hit by intra articular screws during procedures on cervical the vertebrae [7][8][9][10][11][12][13][14][15]. Thus, knowledge on the anatomical variations of the carotid bifurcation (CB) is necessary for the correct interpretation of results obtained by means of different radiological procedures and for vascular surgical procedures in the region mainly because of the significant rates of the occurrence of variations.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the occipital artery can arise from the ICA, and the ascending pharyngeal artery arose from the ICA in a few cases. 1,4) Consequently, segment 1 could further be divided into 2 or 3 parts by the branching points of the proatlantal or hypoglossal artery. Therefore, speculation would suggest that non-bifurcating cervical carotid artery is formed by agenesis of the proximal part of segment 1 using the pharyngo-occipital artery system as a collateral pathway (Table 1, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These variations are important for plastic surgeons to get a bloodless field and to avoid iatrogenic injuries during the reconstructive surgeries of head & neck region and also in cervical lymphadenectomy [2,3].It is of significance to the radiologists in the interpretation of angiograms of head and neck region.The knowledge of the branching pattern of external carotid artery forms the basis for the proper placement of cross clamps on the carotid artery [4] …”
Section: Introductionmentioning
confidence: 99%